If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 0.5x + -7 = x + -5 Reorder the terms: -7 + 0.5x = x + -5 Reorder the terms: -7 + 0.5x = -5 + x Solving -7 + 0.5x = -5 + x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-1x' to each side of the equation. -7 + 0.5x + -1x = -5 + x + -1x Combine like terms: 0.5x + -1x = -0.5x -7 + -0.5x = -5 + x + -1x Combine like terms: x + -1x = 0 -7 + -0.5x = -5 + 0 -7 + -0.5x = -5 Add '7' to each side of the equation. -7 + 7 + -0.5x = -5 + 7 Combine like terms: -7 + 7 = 0 0 + -0.5x = -5 + 7 -0.5x = -5 + 7 Combine like terms: -5 + 7 = 2 -0.5x = 2 Divide each side by '-0.5'. x = -4 Simplifying x = -4
| 4n+8=13 | | 3.5d+8.75=5+4.25d | | -12=2x+6 | | 6h-4=32 | | 5c+8-4d-2-c= | | -3(x+1)+5=2(x-6) | | 2.5d+9.25=1+3.25d | | 8x+1=x+8 | | -16+x=-3x+8 | | 2(4x-1)-5=x-7 | | y-3=2x+2 | | 5+5x=23 | | 5+5+x=23 | | h+14.6=-14.6 | | 4q-q+3q-2q= | | s-5.9=19.2 | | 3(2x+5)=14x+7 | | 6.5=-3+j | | 5(x+1)=6x-11 | | 6a-8=7+a | | -3(2-x)=-15 | | F(x)=x^4-8x^3+18x^2+6 | | 3x-7x+5=3-5x | | 18x-28=x+380 | | 6+0.1x=0.15x+18 | | 10x+24=64 | | x+34+x+34=6x-28 | | 8(2x+1/4)=5(3-4x) | | 2(3m-6+3m)=2m | | 6a-9=6+a | | -5p+49=14 | | 5(k-2)=(3k+9) |